Elemental Analysis of Various Cherry Fruits by Wavelength Dispersive X-Ray Fluorescence Spectrometry - YIGIT, D.; BAYDAS, E.; GULERYUZ, M. (Asian Journal of Chemistry, 2010)
A comperative study on elemental composition of various cherry fruits was conducted by using a sensitive method, wavelength dispersive X-ray fluorescence (WDXRF). Elements such as Na, Mg, Al, Si, Cl, K, Ca, Cr, Fe and Zn were determined in sweet (Prunus avium cv. Napolyon), sour (Prunus cerasus cv. Kütahya) and native cornelian (Cornus mas L.) cherries. Significant differences (p < 0.05 – p < 0.01) were observed in the mineral contents of cherry fruits. The concentration of elements in sour, sweet and cornelian cherry fruits was 1.21, 1.98 and 2.31 % of the total mass, respectively. Na was detected only in cornelian cherry fruits and its level was 150 ppm. The amounts of major elements potassium, magnesium, calcium and phosphor in cherry fruits were ranged to 9267-16778, 1012-2113, 510-2438 and 585-1546 ppm, respectively. The results show that the cherries are rich in the mineral elements that are of importance in man's well being. However, another result with this study shows that the main advantage of this method is the non-modification of the original sample, both during sample preparation and in the exciting X-ray beam.